Answer: hi can I be your friend Step-by-step explanation: Let f(x) = x3 − ax2 + x + 2 It is given that (x − a) is a factor of f(x). ∴ Remainder = f (a) = 0 a3 − a3 + a + 2 = 0 a + 2 = 0 a = −2Read more on Sarthaks.com – https://www.sarthaks.com/149896/find-the-value-of-a-if-x-a-is-factor-of-x-3-ax-2-x-2 Reply

Step-by-step explanation: Let p(x) is polynomial of x . So, p(x) = x^6 – ax^5 + x^4 – ax^3 + 3x -a +2 Given (x-a) is factor of polynomial p(x) x -a =0 So, x = a Put x= a in p(x) P(a) = a^6– a×a^5 + a^4 – a×a^3 + 3a – a +2 = a^6 – a^6 + a^4 – a^4 + 2a + 2 = 2a +2 Here ( x-a) is factor of given polynomial So, remainder must be 0. So, p(a) = 0 2a+2 = 0 Hence value of a = -1 Thank you!! Reply

Answer:hi can I be your friend

Step-by-step explanation:Let f(x) = x3 − ax2 + x + 2 It is given that (x − a) is a factor of f(x). ∴ Remainder = f (a) = 0 a3 − a3 + a + 2 = 0 a + 2 = 0 a = −2Read more on Sarthaks.com – https://www.sarthaks.com/149896/find-the-value-of-a-if-x-a-is-factor-of-x-3-ax-2-x-2

Step-by-step explanation:Let p(x) is polynomial of x .

So, p(x) = x^6 – ax^5 + x^4 – ax^3 + 3x -a +2

Given (x-a) is factor of polynomial p(x)

x -a =0

So, x = a

Put x= a in p(x)

P(a) = a^6– a×a^5 + a^4 – a×a^3 + 3a – a +2

= a^6 – a^6 + a^4 – a^4 + 2a + 2

= 2a +2

Here ( x-a) is factor of given polynomial

So, remainder must be 0.

So, p(a) = 0

2a+2 = 0

Hence value of a = -1

Thank you!!